Elbow Arteriovenous Fistulae. Issue 7 (May 2014) - Wilmink, Teun
Multiple superficial veins in different anatomical configurations exist in the elbow. The resulting variety of elbow arteriovenous fistulae (AVFs) is described in this paper. A classification of elbow AVF in nontransposed AVF, transposed AVF and multiple outflow AVF is proposed. The nontransposed brachiocephalic AVF has the lowest primary failure rate and a good medium-term survival particularly in the elderly. The simplest technique is an end-to-side anastomosis of the median cubital vein to the brachial artery. In cases of small upper arm veins, a perforating vein AVF, using multiple outflow tracts, may be helpful to lower primary failure risk. In the era of vein mapping with portable ultrasound elbow AVF should be made when forearm veins are exhausted or too small. A side-to-side AVF in order to enhance retrograde flow in the median forearm vein seems rarely indicated, in particular considering the greater risk of steal and venous hypertension. A transposed brachiobasilic AVF is a tertiary access procedure after the simpler alternatives have been exhausted. There is conflicting evidence of the benefits of one-stage versus two-stage procedures. Therefore, the type of operation should be tailored to the individual patient.